2013
DOI: 10.1186/1476-511x-12-128
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil ameliorates biomarkers of genotoxicity in an experimental model of spontaneous atherosclerosis

Abstract: BackgroundIt is well known that enhanced production of reactive oxygen species (ROS) leads to oxidative stress observed in atherosclerosis and that ROS can also cause damage in cellular macromolecules, including DNA. Considering previous report that sildenafil, an inhibitor of phosphodiesterase 5 (PDE5), has antioxidant effects, in the present study we evaluated the effect of this drug on genotoxicity of blood mononuclear cells (MNC) and liver cells from atherosclerotic apolipoprotein E knockout mice (apoE-/-)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
29
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 59 publications
8
29
0
2
Order By: Relevance
“…In addition, we demonstrated an exacerbated vasoconstrictor response to sympathetic agonists in the same experimental model, with relative contribution of eicosanoids and ROS using nonselective cyclooxygenase (Cox-1/Cox-2) and NADPH oxidase inhibitors, respectively [18, 20]. In parallel, our laboratories [15, 18, 21-23] and others [24, 25] have published several data supporting the idea that chronic use of sildenafil, a phosphodiesterase 5 (PDE5) inhibitor, improves endothelial function in the apoE -/- mouse. However, the beneficial effects of this drug on the prostanoid vasoconstrictors and on inflammatory cytokines have not yet been evaluated in this suitable animal model of AT [26, 27].…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…In addition, we demonstrated an exacerbated vasoconstrictor response to sympathetic agonists in the same experimental model, with relative contribution of eicosanoids and ROS using nonselective cyclooxygenase (Cox-1/Cox-2) and NADPH oxidase inhibitors, respectively [18, 20]. In parallel, our laboratories [15, 18, 21-23] and others [24, 25] have published several data supporting the idea that chronic use of sildenafil, a phosphodiesterase 5 (PDE5) inhibitor, improves endothelial function in the apoE -/- mouse. However, the beneficial effects of this drug on the prostanoid vasoconstrictors and on inflammatory cytokines have not yet been evaluated in this suitable animal model of AT [26, 27].…”
Section: Introductionmentioning
confidence: 52%
“…In fact, in the present study we observed that treatment of apoE -/- animals with this PDE5 inhibitor reduced the vascular hyperactivity probably by decreasing the TP/ET-1/NADPH oxidase activity. Previous reports from our laboratory and other studies have revealed that sildenafil, besides having vasodilatory effect (by preserving cGMP signaling and consequently reducing [Ca +2 ] c ) presents additional anti-atherosclerotic effects, such as: exhibiting indirect antioxidative and antigenotoxic activity [15, 21, 23], increasing the number and function of endothelial progenitor cells [21], and reducing significantly lipid deposition in the conductance arteries, even under dyslipidemia [15, 18]. Confirming our previous observations, the new finding in this issue is that treatment with sildenafil shifted the exacerbated contractile response to TP and ET-1 close to that exhibited by normal wild-type animals.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have previously demonstrated that ROS overproduction may promote DNA damage through many pathways, since they are well-known genotoxins [6, 22, 23, 67–69]. The novelty of our research is the observation of an increased DNA damage in monocytes of aged and atherosclerotic animals.…”
Section: Discussionmentioning
confidence: 78%
“…The close relationship between inflammation and oxidative damage [6, 15, 22, 63] is supported by previous studies from our group demonstrating that virtually all cells from classical target organs of cardiovascular diseases are affected by ROS overproduction [7, 15, 20–23, 64, 65], mainly by the NADPH oxidases, which also are the main sources of ROS in phagocytic cells [66]. The present findings support the idea that the deleterious effects of ROS are not restricted to hypercholesterolemia and that they may be enhanced by aging, can occur in classical target tissue (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycemia also induces the production of free radicals and promotes the oxidative DNA damage, leading to genomic instability. These DNA damages are responsible for cell cycle arrest, apoptosis, senescence, DNA repair of various cells, and subsequently changes the cardiovascular reactivity [28][29][30]. Hyperglycemia also have correlation with oxidative stress markers such as MDA and DNA damage (comet tail length) in diabetic CAD patients compared to non-diabetic CAD patients indicating its severity on development and progression of CAD.…”
Section: Discussionmentioning
confidence: 99%